A two-tiered demographic system: "Insiders" and "Outsiders" in three Swabian communities, 1558-1914 - Timothy W. Guinnane; Sheilagh C. Ogilvie (Yale University, Economic Growth Center, 2013)
This paper presents first results from a project to reconstitute the demographic behavior of three villages in Württemberg (southern Germany) from the mid-sixteenth to the early twentieth century. Using high-quality registers of births, deaths, and marriages, and unusual ancillary sources, we improve on the family-reconstitution techniques pioneered by Louis Henry and applied to good effect by the Cambridge Group and other scholars. This paper focuses on simple, standard demographic measures, in order to provide a broad overview and support comparisons with other places. An extreme system of demographic regulation operated in these Württemberg communities until around 1870. This regulation created a two-tiered demographic system. A group of insiders were able to marry, and experienced both high marital fertility and high infant and child mortality. A second group of outsiders were prevented from marrying. Many, especially the males, left the community; those who stayed contributed to growing illegitimacy and associated levels of infant and child mortality that were even higher than for the offspring of insiders.
Keywords: N33; J12; J13; K0; O17; 330; fertility; mortality; nuptiality; European marriage pattern; institutions; community; politische Ehekonsens; Germany; Württemberg; proto-industry